2022
DOI: 10.34172/ijhpm.2022.7261
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Regulating Artificial Intelligence in Healthcare Comment on "Clinical Decision Support and New Regulatory Frameworks for Medical Devices: Are We Ready for It? - A Viewpoint Paper"

Abstract: Regulation of health technologies must be rigorous, instilling trust among both healthcare providers and patients. This is especially important for the control and supervision of the growing use of artificial intelligence in healthcare. In this commentary on the accompanying piece by Van Laere and colleagues, we set out the scope for applying artificial intelligence in the healthcare sector and outline five key challenges that regulators face in dealing with these modern-day technologies. Addressing these chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…This allows for more dynamic, emergent behaviors and outcomes, which can provide deeper insights into complex systems, such as oncology trials [ 74 ]. However, medical devices, including AI, need to be approved by regulatory bodies, which requires proving that they are safe and effective [ 75 ], yet many have not been approved. If an AI system is continually changing, it might not remain within the approved parameters.…”
Section: Resultsmentioning
confidence: 99%
“…This allows for more dynamic, emergent behaviors and outcomes, which can provide deeper insights into complex systems, such as oncology trials [ 74 ]. However, medical devices, including AI, need to be approved by regulatory bodies, which requires proving that they are safe and effective [ 75 ], yet many have not been approved. If an AI system is continually changing, it might not remain within the approved parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Some research has found that patients even prefer responses to medical questions from a chatbot to those from a physician, but clearly context matters [ 50 ]. Yet, once again, caution is needed [ 51 ]. Algorithms developed using data from one population may produce misleading results when applied to another [ 41 ].…”
Section: Main Textmentioning
confidence: 99%
“…39 • Regulatory complexity: crafting effective regulations requires a profound understanding of AI systems and associated concepts, necessitating nuanced and sophisticated approaches. 40 • Monitoring and enforcement: establishing clear mechanisms to monitor and enforce compliance with the appropriate regulations poses inherent difficulties. 41 • Evolving threats: addressing the ongoing challenge of keeping pace with increasingly complex potential threats to the misuse of AI systems.…”
Section: Limitations Of Ai Regulationsmentioning
confidence: 99%
“…Several noteworthy downsides of AI regulations include: Balancing between innovation and compliance: striking the delicate equilibrium between allowing for AI system improvements and enforcing strict regulations that prevent abusive use 39 Regulatory complexity: crafting effective regulations requires a profound understanding of AI systems and associated concepts, necessitating nuanced and sophisticated approaches 40 Monitoring and enforcement: establishing clear mechanisms to monitor and enforce compliance with the appropriate regulations poses inherent difficulties 41 …”
Section: Mitigation Measuresmentioning
confidence: 99%